Forced to change: staff and inmate perceptions of involuntary treatment and its effects - Hogan, Nancy L. (Applied psychology in criminal justice, 2015)
The ideological debate over the ability of involuntary programs to modify inmate behavior permeates the treatment literature. Ideology aside, research reveals that programs targeting high-risk offenders are most likely to reduce recidivism even though this group is the least likely to participate voluntarily. With the current economic environment and the continued disappearance of prevention/rehabilitation funding, it may be more cost-effective to target those who need it the most. Interviews were conducted with a sample of inmates involuntarily placed into a Cognitive Housing Approach: New Goals Environment (CHANGE) program as well as the staff who worked with the program. Responses from both inmates and staff support the use of involuntary programs for high risk populations. These qualitative results indicate that behavioral change was occurring for the majority of program participants despite being forced to participate.